ANALISIS KAPASITAS AIR PADA SALURAN DRAINASE DI JALAN ANTASURA DAERAH PEGUYANGAN KAJA DENPASAR UTARA - ANAK AGUNG RATU RITAKA WANGSA; IDA BAGUS SURYATMAJA; I MADE NADA (Universitas Mahasaraswati K. Mataram, 2024)
Drainage is a system created to overcome the problem of excess water above ground and water below ground. The performance of the drainage system is determined by using good construction techniques, carrying out routine and periodic maintenance. Heavy rains not only cause surface water runoff but also urban surface water runoff which forms puddles of water due to the low carrying capacity of the drainage system. One of the areas that experienced flooding in the city of Denpasar was Jalan Antasura in the Peguyangan Kaja area, North Denpasar, which was caused by blockage of channels by sediment caused by rubbish. This research monitors and evaluates rainfall, flood discharge and water capacity in drainage channels. The results of the calculation evaluation and comparison with HEC-RAS modeling show that the water capacity in the drainage channel at the 0-800 m point does not meet the design flood discharge results for all return periods, so it is predicted that the drainage channel will cause flooding, while the water capacity in the drainage channel at the point 800-1000 m still meets the design flood discharge at the 2 year and 5 year return periods, but does not meet the 10 year return period, so it is predicted that the drainage channel will still meet capacity if channel normalization is carried out every year.